The Conditions and Procedure for the Admission of Children of Incarcerated Mothers to Mother-and-Baby Units at Prisons in Poland - Teleszewska, Magdalena (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The admission of mother and child to the a mother-and-baby unit has a positive effect on both the development of the child as well as the social rehabilitation of the mother. Children in mother-and-baby units are provided the right conditions for development. The mother learns to fulfill her parental responsibilities. In addition, incarcerated women who are in prison with their children want to change for the better, in order to provide their children a better future.